Human resource managers' role in the digital era - Alexandra-Paraskevi Chytiri (SPOUDAI - Journal of Economics and Business, 2019)
In any one organization, in Business, Service, Industry or State, Human Resource Management (HRM) is perceived as a set of activities that creates value to both the organization itself in terms of bottom line results and to employees, in terms of well - being and employment/contract terms. Organizations, to a more or lesser extent, have adopted Digital technologies and as a result HR activities are affected, in terms of speed, accuracy, quality, cost innovation, flexibility. The aims of this theoretical study are to highlight HRM in the era of digitalization, emphasize the roles of HR managers in contemporary organizations and discuss the impact of technological changes on HR practices. In order to achieve our aims, we adopt a conceptual approach. Our results summarize the contemporary HRM definitions, discuss the impact of digital technologies in certain HR areas and emphasize the new digital role of human resource manager (d-HRM).
Keywords: O15; M10; 330; Human Resource Management; Role; Digital employee; Digital work; Digital employee management